Autophagy–mediated plasma membrane removal promotes the formation of epithelial syncytia. (9th March 2022) - Kakanj, Parisa; Bhide, Sourabh; Moussian, Bernard; Leptin, Maria
Abstract: Epithelial wound healing in Drosophila involves the formation of multinucleate cells surrounding the wound. We show that autophagy, a cellular degradation process often deployed in stress responses, is required for the formation of a multinucleated syncytium during wound healing, and that autophagosomes that appear near the wound edge acquire plasma membrane markers. In addition, uncontrolled autophagy in the unwounded epidermis leads to the degradation of endo‐membranes and the lateral plasma membrane, while apical and basal membranes and epithelial barrier function remain intact. Proper functioning of TORC1 is needed to prevent destruction of the larval epidermis by autophagy, in a process that depends on phagophore initiation and expansion but does not require autophagosomes fusion with lysosomes. Autophagy induction can also affect other sub‐cellular membranes, as shown by its suppression of experimentally induced laminopathy‐like nuclear defects. Our findings reveal a function for TORC1‐mediated regulation of autophagy in maintaining membrane integrity and homeostasis in the epidermis and during wound healing. Synopsis: Wound healing in Drosophila involves the formation of a multinucleate syncytium. Autophagy elevation leads to selective degradation of the lateral plasma membrane and the formation of a multinucleated syncytium, while the apical and basal membranes and the epithelial barrier function remain intact. Epithelial wounding promotes autophagosome formation. Autophagy is necessary and sufficient to induce syncytium formation in the healthy epithelium and during wound healing. The TORC1/autophagy pathway controls plasma membrane integrity. The destruction of plasma membrane that is kept in check by the TORC1/autophagy pathway requires phagophore initiation and expansion but not fusion to lysosomes. The lateral plasma membrane is a potential source of autophagosomal membranes. Abstract : Elevated autophagy induces syncytium formation by membrane breakdown in the epidermis and during wound healing in Drosophila .